Evaluation of Naringenin as a Promising Treatment Option for COPD Based on Literature Review and Network Pharmacology - Zhen Chen; Pan Chen; Hao Wu; Rui Shi; Weiwei Su; Yonggang Wang; Peibo Li (Biomolecules, 2020)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease characterized by incompletely reversible airflow limitation and seriously threatens the health of humans due to its high morbidity and mortality. Naringenin, as a natural flavanone, has shown various potential pharmacological activities against multiple pathological stages of COPD, but available studies are scattered and unsystematic. Thus, we combined literature review with network pharmacology analysis to evaluate the potential therapeutic effects of naringenin on COPD and predict its underlying mechanisms, expecting to provide a promising tactic for clinical treatment of COPD.